Neutrophil Percentage-to-Albumin Ratio: A Good Parameter for the Evaluation of the Severity of Anti-NMDAR Encephalitis at Admission and Prediction of Short-Term Prognosis - Tang, Yao; Hou, Haiman; Li, Lanjun; Yong, Liuliang; Zhang, Shuang; Yan, Lulu; Huang, Xiaoxue; Wu, Jun (Frontiers in Immunology, 2022)
Objectives: The purpose of this study was to investigate the association of neutrophil percentage to albumin ratio (NPAR) with the severity at admission and dischagre (short-term prognosis) in patients with anti-N-methyl-D-aspartic acid receptor (NMDAR) encephalitis. Methods: Multivariate logistic regression models such as NPAR were constructed based on univariate regression results. ROC curves, nomograms and concordance index (c-index) were used to evaluate the efficacy of the models in assessing disease severity at admission and predicting short-term prognosis, with validated by Bootstrap, Hosmer-Lemeshow goodness-of-fit test, calibration curves and decision curve analysis. Results: NPAR has good sensitivity and specificity in assessing the disease severity at admission and predicting short-term prognosis. The multivariate logistic regression model based on NPAR and other influencing factors have good discrimination, consistency, accuracy, calibration ability, applicability and validity in assessing the severity at admission and predicting short-term prognosis. Conclusion: NPAR has good clinical value in assessing disease severity at admission and predicting short-term prognosis of patients with anti-NMDAR encephalitis.